Al Faruqi and Beyond - Ilyas Ba-Yunus (International Institute of Islamic Thought, 1988)
Ismlil was born in an influential family in 1341 AH/1922 AC in Palestine during the British Mandate. He received his early education in traditional Islamic schools and his college education from the American University, Beirut. At age 24, he was appointed as governor of Gallilee-the last Palestinian, before the Zionist occupation. Forced to migrate, his family took refuge in neighboring Lebanon. Having thus experienced this “fall” at the very onset of what was promising to be a brilliant political career in an otherwise independent Palestine, the refugee in Isma’il tumed toward the higher reaches of modem education in the contemporary West. Ismlil concentrated in philosophy first at Harvard and then at Indiana, where he earned his doctoral degree. He spent four years at Al Azhar in Egypt, followed by two years at the School of Divinity at McGill, and two years at the newly established Islamic Research Institute in Islamabad, Pakistan, which gave him ample opportunity to apply his philosophy to religion or, more appropriately, to apply his religion to modem secular philosophy. This is what gave “the wounded Palestinian” a new weapon with which to start on a course of an intellectual encounter with the West. His books on On Arabism, The Origins of Zionism in Judaism, and The Christian Ethics came in a succession in the 1960’s. Naturally, as Rahman (1406 AH/1986 AC) pointed out, while involved in this undertaking, he disturbed some and antagonized others. What is amazing is that in doing this, the “Arab Warrior” conquered himself ...